Addressing Stillbirth in India Must Include Men. (3rd July 2017) - Roberts, Lisa; Montgomery, Susanne; Ganesh, Gayatri; Kaur, Harinder Pal; Singh, Ratan
ABSTRACT: Background: Millennium Development Goal 4, to reduce child mortality, can only be achieved by reducing stillbirths globally. A confluence of medical and sociocultural factors contribute to the high stillbirth rates in India. The psychosocial aftermath of stillbirth is a well-documented public health problem, though less is known of the experience for men, particularly outside of the Western context. Therefore, men's perceptions and knowledge regarding reproductive health, as well as maternal-child health are important. Methods: Key informant interviews (n = 5) were analyzed and 28 structured interviews were conducted using a survey based on qualitative themes. Results: Qualitative themes included men's dual burden and right to medical and reproductive decision making power. Wives were discouraged from expressing grief and pushed to conceive again. If not successful, particularly if a son was not conceived, a second wife was considered a solution. Quantitative data revealed that men with a history of stillbirths had greater anxiety and depression, perceived less social support, but had more egalitarian views towards women than men without stillbirth experience. At the same time fathers of stillbirths were more likely to be emotionally or physically abusive. Predictors of mental health, attitudes towards women, and perceived support are discussed. Conclusions: Patriarchal societal values, son preference, deficient women's autonomy, and sex-selective abortion perpetuate the risk for future poor infant outcomes, including stillbirth, and compounds the already higher risk of stillbirth for males. Grief interventions should explore and take into account men's perceptions, attitudes, and behaviors towards reproductive decision making.